RANCANG BANGUN GAME EDUKASI ‘DEN SARWO’ BERBASIS MOBILE MATA PELAJARAN BAHASA JAWA MATERI AKASARA JAWA DI KELAS IVB SD NEGERI MOJOSONGO 3 - Wardana, Sandra Kurnia; Sufa, Feri Faila; Hapsari, Alfonsa Maria Sofia (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2023)
The purpose of this research is to design a mobile-based educational game "Den Sarwo" on Javanese language subjects on Javanese script material to help students to understand Javanese script. Researchers used the Research and development (R&D) method with the ADDIE development model. Data collection using interviews, questionnaires, and documentation. Testing of the educational game "Den Sarwo" was carried out using the Blackbox Testing method and validation by experts who were converted using a Likert Scale. The results showed that the educational game "Den Sarwo" obtained very feasible criteria according to media experts having a feasibility level of 92%, according to material expert validation having a feasibility level of 92% with very feasible criteria, and feasibility assessment by educators getting a percentage of 97.3% with very feasible criteria, so that the educational game "Den Sarwo" is feasible to use as a learning media and entertainment facility when studying independently anytime and anywhere.